Possibilities of using inclusive growth in ensuring sustainable development in the Republic of Uzbekistan (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
In this article, the conditions of sustainable development, the description of "inclusiveness" and "inclusive growth" by the producers and the government of the Republic of Uzbekistan, as well as the possibilities of inclusive growth in ensuring sustainable development in Uzbekistan are analyzed, and relevant comments are made